The Value of Unveiling the Experiences of Black-Owned Businesses in South Africa in the Construction Sector - Dladla, Nomathemba (University of the Witwatersrand, Johannesburg, 2015)
This research report mainly focuses on how planners can influence policy with regards to economic empowerment from a construction point of view. To obtain a better understanding of how economic empowerment is translated in the South African context, it is paramount to scrutinise the policies and strategies that have been set in place. The report engages with concepts such as entrepreneurialism and business ownership that have been discussed by authors such as Southall and Rogerson. With the understanding of such concepts, a theoretical foundation is set, that enables the author to create a conceptual framework that visualises how economic empowerment is meant to pan out in reality and at a small scale. Not only does this report discuss and analyse the theoretical understanding of economic empowerment, but it also studies the personal experiences of business owners in the construction sector. The reason why the personal experiences of business owners are prioritised in this study is because they are used as a tool to determine how far or close the existing set strategies are from an individual’s reality. Soweto has been used as the case study to closely analyse economic empowerment through life experiences. The findings produced in this case study therefore create a basis for the way forward, in which planners could possibly adapt to help improve policy.
Planning Honours Report 2015, Wits University